2011
DOI: 10.1111/j.1467-8543.2011.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Working Hours in Supply Chain Chinese and Thai Factories: Evidence from the Fair Labor Association's ‘Soccer Project’

Abstract: This article examines the determinants of working excessive hours, defined as working in excess of 60 hours per week or for more than six consecutive days, in Chinese and Thai supply chain factories. We use a matched employeremployee dataset collected from 15 Chinese and Thai footwear and sporting apparel supply chain factories, which supply international brands. Matched employer-employee data allow us to examine the effect of worker and firm characteristics on hours worked. We find that in addition to the dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…One existing study for China that does consider the employer dimension is Smyth et al . 's (). That study uses matched employer and employee data from the Fair Labor Association (FLA) to examine the correlates of excessive hours worked in Chinese and Thai supply chain factories.…”
Section: Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…One existing study for China that does consider the employer dimension is Smyth et al . 's (). That study uses matched employer and employee data from the Fair Labor Association (FLA) to examine the correlates of excessive hours worked in Chinese and Thai supply chain factories.…”
Section: Existing Literaturementioning
confidence: 99%
“…Our study differs from Smyth et al . () in four respects. First, that study focused on the determinants of excessive hours worked, defined as in excess of 60 hours per week, while we look at the determinants of hours worked more generally.…”
Section: Existing Literaturementioning
confidence: 99%
“…In a recent survey of Chinese workers, for example, respondents pointed to long work hours as one of three major reasons for health problems (Tang, 2013). Some therefore argue that the unprecedented economic growth in China may have taken place on the back of employees working long hours (Smyth, Qian, Nielsen, & Kaempfer, 2013). As stated by Kingston (cited in Oster, 2014), due to the Confucian belief in total dedication, Chinese employers are prone to overburden their employees.…”
Section: Introductionmentioning
confidence: 99%
“…Second, living conditions in factory dormitories are often poor (Smith and Pun 2006). In particular, long working hours and lack of work-life divide associated with living on site in a factory dormitory can result in psychological problems, which are associated with a higher proclivity to engage in gambling (Smyth et al 2013). In several studies, gamblers have reported that gambling represents an avenue, albeit tem porarily, to distract them from problems and worries (Petry 2005).…”
Section: {Continued)mentioning
confidence: 99%